Augmented Reality-based ecolabel model for environmental awareness. Issue 5 (March 2021) - Safitri, D; Marini, A; Yunaz, H; Putra, ZE F F; Nuraini, S; Rihatno, T; Ibrahim, N
Abstract: The purpose of this research is to develop Augmented Reality-based ecolabel model for environmental awareness. This research and development were done in Jakarta, the capital city of Indonesia. The product of this research is augmented reality called ecolabel on the Android Smartphone having eight logos to give environmental awareness to the consumers. This product giving the consumers some 2-dimension information containing accurate, fast, verifiable, and not misleading information related to environmental aspect of the certain products. This product should be supported by sticker as marker to turn on augmented reality. Consequently, the society will be more appropriate in making decision to choose the product used. Revision on the basis of expert validation reaching 3, 67 from maximum score 4 is that pictures given to the nine logos in this product should be added more to provide more examples to the consumer. The conclusion of this research is that Augmented Reality-based ecolabel model for environmental awareness is already valid.